Rahmah El-Yunusiyah: Women's Leadership through Educational Institutions - Nasrun Harahap (AT-TA'LIM, 2025)
Women's leadership in education is an interesting topic of study. Among the figures recorded in educational history is Rahmah El Yunusiyah through educational institutions. In the Minangkabau era, women were viewed as having a very low status; they were treated like objects that could be treated as one pleased, exchanged, and even inherited. In fact, the community at that time considered the birth of a daughter to be something shameful for the family, so they eliminated them by burying them alive. The research method used was field research, involving observation and interviews in the field related to educational concepts. The figures' acknowledgments and explanations of Rahmah's personality were then analyzed using descriptive analytical research. The data was then analyzed using qualitative methods. Rahmah El Yunusiah brought modern thinking to the world of education. The rector of al-Azhar, Sheikh Abdur Rahman Taj, who was very humble, greatly admired Rahmah El Yunusiah because she founded Diniyah Putri in Padang Panjang, which was the first school in the world specifically for girls. This school inspired the Rector of Al-Azhar to establish a faculty at his university specifically for women. The Rector also awarded the first Doctorate degree to Rahmah EL-Yunusiah for her knowledge, achievements, and dedication in fighting for women in the world of education. The results of the research show that: 1) According to Rahmah El-Yunusiah, education must have the same rights as men, women must reflect noble behavior/morals starting from home, love for the country and nation also starts from home. Women have a role in the household that requires four tendencies that they must embody, namely as mothers to their children, as educators, as lovers to their husbands, and as friends to their families. 2) As a leader of women, she desires prosperity for women, participating in community service and da'wah in an effort to promote good deeds and prevent evil. Women are not prohibited from participating in politics as long as their vision and mission are to fight for truth and the welfare of the general public.